14.1k views
5 votes
Use the system of equations to answer the questions. 2x + 3y = 3 y = 8 – 3x The value of y from the second equation is substituted back into the first equation. What is the resulting equation? What is the value of x? What is the value of y?

User Harolyn
by
5.1k points

2 Answers

1 vote

Answer:

the correct answers for edu are 2x+3(8-3x)=3 than 3 and last -1

Explanation:

User Qudusayo
by
5.6k points
4 votes

Answer:

  • 2x +3(8 -3x) = 3
  • x = 3
  • y = -1

Explanation:

The second equation tells you ...

y = 8 -3x

Using this expression in the first equation gives you ...

2x +3(8 -3x) = 3

2x +24 -9x = 3 . . . . . eliminate parentheses

21 = 7x . . . . . . . . . . . add 7x -3

3 = x . . . . . . . . . . . . . . divide by 7

y = 8 -3×3 = -1 . . . . . . use the second equation to find y

The solution is (x, y) = (3, -1).

User Erikfas
by
4.7k points